PerancanganRefunction ContainerSebagai Modular Retail di Surabaya - Yusita Kusumarini, Boris Kumara (Intra, 2015)
The business world that built by entrepreneurs will encourage the development of productive sectors. Retail sector and shopping centers have proven to provide a positive contribution to the economic recovery in Indonesia. Shipping containers can be applied as an alternative to building with affordable price. Designed by the method of modularity sothey could build in a short period of time, and allows it to be combined into larger structures. Business world is very dynamic, so it also needed a business tools to support that dynamical trait. Accordingly, it is hoped that the design of refunctioncontainer as a modular retail in Surabaya can be an building alternative that has many advantages and benefits for the entrepreneurs concerned